Application of recycled ceramics from wastes for high temperature thermal energy storage - Ong, Ton Chee Yung (Nanyang Technological University, 2020)
The aim of this project is to explore the application of recycled ceramics from wastes for high temperature Thermal Energy Storage. Air Pollution Control ash was collected from a Municipal Solid Wastes Incineration plant in Tuas Singapore. The target was to explore the suitability of treating APC ash with washing and sintering as possible treatment methods to convert it to a Sensible Heat Thermal Energy Storage material. Varying wash duration of 1, 4 and 24 hours with deionised water with Liquid-to-Solid ratio of 5, 10 and 20 were carried out. For APC ash treated under washing duration of 1 and 4 hours, the samples showed significant weight lost around 400 °C to 750 °C in Thermogravimetric graphs, where material weight loss versus temperature graphs were being plotted. However, better stability was achieved after a 24-hour wash was carried out. This could be due to the high chloride contents present in APC, which absorbs moisture and may have caused the instability, after it was washed off, resulting in reduction of NaCl, KCl and CaCl2. However, enthalpy is relatively low, hence extra treatment process like sintering is needed. After the sintering process, heat capacity was measured to be approximately 2 J/g.°C at temperature reaching 306.85 °C. Unexpectedly, an endothermic reaction occurred thereafter. Through XRD investigation, this endothermic reaction was due to the presence of CaO, which was the dominant mineral after sintering washed APC ash at 800 °C for 2 hrs. Although the APC is no longer considered a Sensible Heat Thermal Energy Storage material for high temperature, this latent heat of 151.3 J/g can be a potential Thermochemical storage material instead.